Volatile MoS2 Memristors with Lateral Silver Ion Migration for Artificial Neuron Applications - Sofía Cruces; Mohit Dineshkumar Ganeriwala; Jimin Lee; Lukas Völkel; Dennis Braun; Annika Grundmann; Ke Ran; Enrique González Marín; Holger Kalisch; Michael Heuken; Andrei Vescan; Joachim Mayer; et al. (Small Science)
Layered 2D semiconductors have shown enhanced ion migration capabilities along their van der Waals (vdW) gaps and on their surfaces. This effect can be employed for resistive switching (RS) in devices for emerging memories, selectors, and neuromorphic computing. To date, all lateral molybdenum disulfide (MoS2)‐based volatile RS devices with silver (Ag) ion migration have been demonstrated using exfoliated, single‐crystal MoS2 flakes requiring a forming step to enable RS. Herein, present volatile RS with multilayer MoS2 grown by metal‐organic chemical vapor deposition (MOCVD) with repeatable forming‐free operation is presented. The devices show highly reproducible volatile RS with low operating voltages of ≈2 V and fast‐switching times down to 130 ns considering their micrometer‐scale dimensions. The switching mechanism is investigated based on Ag ion surface migration through transmission electron microscopy, electronic transport modeling, and density functional theory. Finally, a physics‐based compact model is developed and the implementation of the volatile memristors as artificial neurons in neuromorphic systems is exploredd.